أثر كفاءة وفعالية منظمات المجتمع المدني التنموية في تحقيق التنمية المستدامة من خلال التنمية الاقتصادية: دراسة تطبيقية على أمانة العاصمة صنعاء - عاصم علي حسن الشرفي
This study aims to verify the implications of the efficiency and effectiveness of civil society development organizations in the Capital Municipality, Sana'a Province to achieve sustainable development through econonic development. In the current study, the researcher used descriptive, analytical methods to achieve the research goals and test the hypotheses. The study was basede on a number of management and sociological theories, of which the most significant is the modernization theory. The study sample was composed of (208) members of civil society development organizations working in the Capital Municipality, Sana'a Province For the purpose of anlayzing the collected data, the researcher used SPSS to analyze the descriptive data and the prelimeneray survey of teh data. It was followed by structural equation models. Through using a Smart-PLS program, it is possible to test a group of complex variables at the same time, taking into account calculations if any median variable found. The analysis concluded that there is an obvious disparity in the role played by civil society development organization in the Capital Muncipality, adn their policies to accomplish sustainable development. It is indicative of the inablility to reach a sufficient level of efficiency and effectiveness to meet all aspiration of the local community in Yemen. In regard with the median variable, it was found that the economic development plays a mediating role in the relationship between efficiency and efficacy of an organization and the achievement of sustainable development. Thus, the study recommends that periodic trainings should be given to field and administrative personnel of these organizations in coordination with international organizations working in Yemen and official bodies. A joint network and joint leadership among development organizations ought to be created to unify and coordinate efforts to achieve a better level of efficiency and effectiveness. This study offers theoritical and practical contributions to provide a current model and a good picture of the implications that may help in achieving sustainable development.